Transformasi Budaya Organisasi: Menuju Organisasi Yang Adaptif Dan Modern - Dini Vientiany; Aulia Hafsah Pane; Usna Nur Indah; Delvi Salwa Nakita (Journal of Management and Creative Business, 2024)
Organizational culture is a pattern of beliefs and values that are understood, internalized, and practiced by an organization. Every organization has a unique culture that characterizes the organization which has an important role because a good culture provides comfort and supports the performance of members. In the modern era, in order for the organization to continue to run and survive, the organization must be able to adapt, one of which is by transforming or changing the culture in the organization itself. The success of the transformation can be measured by how the organization overcomes and reduces the risk of resistance that is likely to arise from its members.